Study of the immunologic response of marine-derived collagen and gelatin extracts for tissue engineering applications. (15th March 2022) - Alves, A.L.; Costa-Gouveia, J.; Vieira de Castro, J.; Sotelo, C.G.; Vázquez, J.A.; Pérez-Martín, R.I.; Torrado, E.; Neves, N.; Reis, R.L.; Castro, A.G.; Silva, T.H.
Abstract: The host immunologic response to a specific material is a critical aspect when considering it for clinical implementation. Collagen and gelatin extracted from marine sources have been proposed as biomaterials for tissue engineering applications, but there is a lack of information in the literature about their immunogenicity. In this work, we evaluated the immune response to collagen and/or gelatin from blue shark and codfish, previously extracted and characterized. After endotoxin evaluation, bone marrow-derived macrophages were exposed to the materials and a panel of pro- and anti-inflammatory cytokines were evaluated both for protein quantification and gene expression. Then, the impact of those materials in the host was evaluated through peritoneal injection in C57BL/6 mice. The results suggested shark collagen as the less immunogenic material, inducing low expression of pro-inflammatory cytokines as well as inducible nitric oxide synthase (encoded by Nos2 ) and high expression of Arginase 1 (encoded by Arg1 ). Although shark gelatin appeared to be the material with higher pro-inflammatory expression, it also presents a high expression of IL-10 (anti-inflammatory cytokine) and Arginase (both markers for M2-like macrophages). When injected in the peritoneal cavity of mice, our materials demonstrated a transient recruitment of neutrophil, being almost non-existent after 24 hours of injection. Based on these findings, the studied collagenous materials can be considered interesting biomaterial candidates for regenerative medicine as they may induce an activation of the M2-like macrophage population, which is involved in suppressing the inflammatory processes promoting tissue remodeling. Statement of significance: Marine-origin biomaterials are emerging in the biomedical arena, namely the ones based in marine-derived collagen/gelatin proposed as cell templates for tissue regeneration. Nevertheless, although the major cause of implant rejection in clinical practice is the host's negative immune response, there is a lack of information in the literature about the immunological impact of these marine collagenous materials. This work aims to contribute with knowledge about the immunologic response to collagen/gelatin extracted from blue shark and codfish skins. The results demonstrated that despite some differences observed, all the materials can induce a macrophage phenotype related with anti-inflammation resolution and then act as immuno-modulators and anti-inflammatory inducible materials. Graphical abstract: Image, graphical abstract